2019
DOI: 10.1111/bph.14702
|View full text |Cite
|
Sign up to set email alerts
|

The G‐protein‐biased agents PZM21 and TRV130 are partial agonists of μ‐opioid receptor‐mediated signalling to ion channels

Abstract: Background and Purpose Opioids remain the most efficient medications against severe pain; they act on receptors that couple to heterotrimeric G‐proteins in the Gαi/o family. Opioids exert many of their acute effects through modulating ion channels via Gβγ subunits. Many of their side effects are attributed to β‐arrestin recruitment. Several biased agonists that do not recruit β‐arrestins, but activate G‐protein‐dependent pathways, have recently been developed. While these compounds have been proposed to be ful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 43 publications
7
41
0
Order By: Relevance
“…We observed that PS responses were rapidly and reversibly inhibited by DAMGO in about 50% of the hSCDS neurons. Such a variable inhibition of TRPM3 by μ‐opioid receptor activation was also reported in isolated mouse sensory neurons, where PS responses were insensitive to DAMGO or morphine in between 5% and 30% of the neurons (Dembla et al, ; Quallo et al, ; Yudin & Rohacs, ). The variable inhibition of the TRPM3 responses may reflect the unequal expression of the μ‐opioid receptor or its downstream signalling pathway in sensory neurons.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…We observed that PS responses were rapidly and reversibly inhibited by DAMGO in about 50% of the hSCDS neurons. Such a variable inhibition of TRPM3 by μ‐opioid receptor activation was also reported in isolated mouse sensory neurons, where PS responses were insensitive to DAMGO or morphine in between 5% and 30% of the neurons (Dembla et al, ; Quallo et al, ; Yudin & Rohacs, ). The variable inhibition of the TRPM3 responses may reflect the unequal expression of the μ‐opioid receptor or its downstream signalling pathway in sensory neurons.…”
Section: Discussionmentioning
confidence: 55%
“…In rodents, it has been previously shown that TRPM3 activity is suppressed following activation of a variety of GPCRs, including the μ‐opioid receptor, via a mechanism involving the G βγ subunit of trimeric G proteins (Badheka et al, ; Dembla et al, ; Quallo et al, ; Yudin & Rohacs, ). Considering the role of TRPM3 in nociception, it has been proposed that this pathway could contribute to the analgesic effects of peripheral opioids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular the following rank order of maximal effects was determined: DAMGO = fentanyl = methadone > morphine = oxycodone > oliceridine = PZM21 ≥ SR-17018 ≥ buprenorphine which was highly conserved in all the assays (r 2 always ≥ 0.79) including ligand-induced C-terminal phosphorylation of the mu receptor. Of note is that the partial agonist behavior of PZM21 and oliceridine at the mu receptor has already been reported for ion channel signaling using electrophysiological and Ca 2+ imaging techniques [ 65 ] and in biochemical assays (Azzam et al personal communication). Surprisingly, this same rank order of maximal effects was measured in receptor regulatory pathway assays (GRK2 and βarr2 and receptor internalization) for all compounds; thus, suggesting that they have similar activity in both G protein and receptor regulatory pathways.…”
Section: Pharmacological Studies—are Mu Receptors Partial Agonistsmentioning
confidence: 95%